A Proposed Model For Antecedents and Consequences of Customers’ Satisfaction With Banks: Field Study To Egyptian Commercial Banks and Foreign Commercial Banks Working In Egypt - Barakat , Mohamed (The Arab Journal of Administration, 2019)
Research problem can represented as follows: some managers of Egyptian commercial banks and foreign commercial banks working in Egypt do not perceive both antecedents and consequences of customers’ satisfaction with banks adequately. This research aims to build and test a model for antecedents and consequences of customers’ satisfaction with banks in Egypt and to provide the recommendations that may increase customers’ satisfaction with banks. Researcher used inductive approach to set research hypotheses and deductive approach to test the research hypotheses. Researcher drew intercept sample from banks’ customers population. Sample size is 384 customers. The number of valid questionnaires is 330.The Rate of Response is 85.93%. The researcher used alpha cronbach analysis to test the reliability of scales of the research. The researcher used confirmatory factor analysis to test the validity of scales of research. The researcher used path analysis to test the validity of the proposed conceptual framework as whole. The researcher used regression analysis to test the significance of the relationships among the factors of research. The Research Findings indicated that the main determinants of customers’ satisfaction with banks are bank’s market orientation and perceived service quality and the main consequences of customers ‘satisfaction with banks are customer’s loyalty to bank and bank’s reputation. The research findings revealed also that there is a significant and positive relationship between bank’s market orientation, perceived service quality and customer’s satisfaction with bank. The research results indicated too that there is a significant and positive relationship between customer ‘s satisfaction with bank and customer loyalty to bank and there is a significant and positive relationship between bank’s market orientation, customer’s satisfaction with bank and bank’s reputation.